2010
DOI: 10.1109/tmtt.2010.2041576
|View full text |Cite
|
Sign up to set email alerts
|

Accurate EM-Based Modeling of Cascode FETs

Abstract: Cascode field-effect transistors (FETs) are widely used in the design of monolithic microwave integrated circuits (MMICs), owing to their almost unilateral and broadband behavior. However, since a dedicated model of the cell is rarely provided by foundries, a suboptimal description built by replicating the standard foundry model for both the common source and common gate device is often adopted. This might limit the success of the MMIC design at the first foundry run. This paper describes an electromagnetic-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It can be found that L gx and L dx are very close and 2-3 times than L sx roughly. Figure 7 shows the extracted results for packaging capacitances C gx and C dx versus frequency at two different bias conditions (I ds 510 mA and 16 mA) by using (16) and (17). A remarkable flat frequency response can be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that L gx and L dx are very close and 2-3 times than L sx roughly. Figure 7 shows the extracted results for packaging capacitances C gx and C dx versus frequency at two different bias conditions (I ds 510 mA and 16 mA) by using (16) and (17). A remarkable flat frequency response can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although the direct extraction methods has been widely used for on-wafer FETs small signal model, however, these methods are not suitable for the determination of model parameters for packaged devices and have to be improved therefore [15,16]. Alternatively, a distributed parasitic network description based on electromagnetic (EM) simulation is adopted and used in conjunction with a conventional active device model [17]. The drawback is the geometric size of packaging is necessary to know in detail for EM simulation and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic portion of a standard two-finger test HEMT is extracted with a combination of an extended form of the EM extrinsic treatment in [3][4][5] for a single gate finger and the robust extraction technique of [6].…”
Section: Device Deconstructionmentioning
confidence: 99%
“…Ports 1 and 2 are the external measurement ports, while internal ports 3 to 4N+2 represent the differential gate-source and gate-drain ports of the intrinsic devices. In contrast to [3][4][5], the differential ports used here allow the impedance seen by all intrinsic device ports to vary according to the metal defining the manifold. This permits all the metal in the symmetric test device layout to be algebraically deembedded from measured s-parameters, immediately yielding the device parameters without any compaction, optimisation or iteration.…”
Section: Device Deconstructionmentioning
confidence: 99%
See 1 more Smart Citation